The importance of transportation networks and urban services in assessing the functional balance of human settlements: The case of the Makkah region in Saudi Arabia - Amani Derbali; Salma Dwidar; Amal Abdelsattar; Donia Abdelgawad; Abdallah Farhi (Transportation Research Interdisciplinary Perspectives)
Saudi Arabia’s 2030 Vision aims to accommodate 30 million Umrah pilgrims by 2030, while promoting sustainable cities through improved mobility in public spaces. This research assesses the balance and future stability of human settlements within the urban system of the Holy Makkah Province. Our investigation highlights the limitations of the region’s urban structure and suggests solutions for addressing their root causes by comparing the current state of the region’s population, which houses 132 urban centers, and an alternative model based on a gravitational urban law utilizing Reilly’s law of retail gravitation (1931), which manipulates data relevant to population and transportation networks. The investigation is then enhanced by additional factors such as the functional weight, retail services, and services related to pilgrims’ rituals. Our theory posits that Makkah Province is subject to the issue of urban primacy, evinced by the fact that the region receives a disproportionate share of the nation’s resources and services. This hierarchal study reveals potential gaps that require attention, as well as actions for the long-term preservation of the region’s urban balance, providing a more comprehensive understanding of future infrastructure amenities and services requirements. We suggested a participatory redistributive approach aiming to foster engagement of marginalized centers and attend to urban–rural linkages, which can serve the urban goals of the 2030 vision through a well-established urban infrastructure and equitable access to services for the regional population.